Multisite Inhibition of Pinus pinea Isocitrate Lyase by Phosphate - Ranaldi, Francesco (American Society of Plant Physiologists, 2000)
Our results show that the phosphate ion is a nonlinear competitive inhibitor of Pinus pinea isocitrate lyase. In addition, this compound induces a sigmoidal response of the enzyme, which usually exhibits standard Michaelis-Menten kinetics. This peculiar behavior of P. pinea isocitrate lyase could be explained by a dimer (two-site) model, in which phosphate binds cooperatively, but the affinity of the vacant site for substrate (the magnesium-isocitrate complex) remains the same. As a result, the interaction of phosphate with free enzyme produces an inhibitor-enzyme-inhibitor species that is of significant importance in determining reaction rate; a possible regulatory role of the glyoxylate cycle by inorganic phosphate is suggested. The mode of phosphate inhibition is consistent with both the mechanism for magnesium ion activation of P. pinea isocitrate lyase and its site heterogeneity. Our results explain the cooperative effects observed by some authors in kinetic studies of isocitrate lyase carried out in phosphate buffers and also account for the higher K(m) values determined by using such assay systems. Phosphate buffer should be avoided in performing isocitrate lyase kinetics.